High-power and widely tunable mid-infrared optical parametric amplification based on PPMgLN - Peng, Yuefeng; Wei, Xingbin; Luo, Xingwang; Nie, Zan; Peng, Jue; Wang, Yong; Shen, Deyuan (Optics letters, 2016)
We report on a high-power and widely tunable optical parametric amplifier (OPA) based on PPMgLN and pumped by a pulsed 1.064 μm MOPA laser. The operating wavelength of the OPA system is continuously tunable from 2.68 to 3.07 μm by adjusting the temperature of PPMgLN crystals, with average output power varying from 74.6 to 66.7 W for 310 W of pump power, corresponding to an optical-to-optical conversion efficiency of ∼22.8% at 2.68 μm and ∼20.5% at 3.07 μm, respectively. Output beam quality factor (M ) of the OPA was measured to be <4 over the whole tuning range.